Results from Bottom Trawl Survey on Flemish Cap of July 2013 - Mandado, Mónica (Northwest Atlantic Fisheries Organization, 2014)
60 páginas, 13 figuras, 41 tablas.-- Scientific Council Meeting A stratified random bottom trawl survey on Flemish Cap was carried out from 26th June to 23th July 2013, covering the bank up to 1460 m depth (800 fathoms). The survey was carried out on board R/V Vizconde de Eza, using a Lofoten bottom trawl gear, and 181 haul were done, 120 of them in the region with less than 730 m depth. Survey results are presented and compared with results of previous surveys in the series since 1988. Biomass and abundance indices are provided for main commercial species, as well as age composition for cod, American plaice, redfish, Greenland halibut, roughhead grenadier and shrimp This study was supported by the European Commission (Program for the Collection of Data in Fisheries Sector), IEO, IPMA and CSIC.